Structural changes in the lacrimal sac epithelium and associated lymphoid tissue during experimental dacryocystitis - Yoshitomi T (Dove Medical Press, 2011)
Makoto Ishikawa1, Masabumi Kubo2, Seiji Maeda3, Yu Sawada1, Eiichi Uchio4, Takeshi Yoshitomi11Department of Ophthalmology, Akita University School of Medicine, Akita, Japan; 2Fukiage Eye Clinic, Hachinohe, Japan; 3Maeda Eye Clinic, Honjo, Japan; 4Department of Ophthalmology, Fukuoka University School of Medicine, Fukuoka, JapanPurpose: To examine structural changes in the lacrimal sac epithelium and associated lymphoid tissue of rabbits with experimentally induced dacryocystitis.Methods: Experimental dacryocystitis was induced by an inoculation of Staphylococcus aureus into the lacrimal sac. The histological changes of the inflamed lacrimal sac epithelium and associated lymphoid tissue were studied by light and electron microscopy.Results: After 1 month, numerous inflammatory cells (CD20-positive B lymphocytes, CD3-positive T lymphocytes, IgA-positive plasma cells, and polymorphonuclear leukocytes) infiltrated the lamina propria and the epithelium overlying the diffuse lymphoid tissue. Three months later, the density of the infiltrated leukocytes was markedly decreased. The epithelial lining overlying the diffuse lymphoid tissue became thicker with numerous secretory granules in the supranuclear regions.Conclusion: The lacrimal sac epithelium and associated lymphoid tissue play a major role in the defense mechanism during inflammation. Overproduction of secretory granules after bacterial inoculation could enhance the antimicrobial defense.Keywords: experimental dacryocystitis, lacrimal sac epithelium, lymphoid tissue, structure, rabbit